Rethinking Path Creation: A Geographical Political Economy Approach. (15th March 2019) - MacKinnon, Danny; Dawley, Stuart; Pike, Andy; Cumbers, Andrew
Abstract: A burgeoning strand of evolutionary economic geography (EEG) research is addressing questions of regional path creation, based on the idea that place-specific legacies and conditions play a critical role in supporting the emergence of new economic activities. Yet there has been little effort thus far to take stock of this emerging body of research. In response, the aims of this article are to offer a fresh synthesis of recent work and to develop a broader theoretical framework to inform future research. First, it presents a critical appraisal of the state of the art in path creation research. In an effort to address identified gaps in EEG research, this incorporates insights from sociological perspectives, the global production networks approach, and transition studies. Second, the article's development of a systematic theoretical framework is based on the identification of key dimensions of path creation and their constitutive interrelations. This contribution is underpinned by a geographical political economy (GPE) approach that provides the ontological basis for the integration of the five key dimensions of path creation within an overarching framework and the positioning of regional processes in relation to the broader dynamics of uneven development. Informed by GPE, the argument is that knowledgeable actors, operating within multiscalar institutional environments, create paths through the strategic coupling of regional and extraregional assets to mechanisms of path creation and associated markets. To inform further research, the article outlines four concrete propositions regarding the operation of path creation processes in different types of regions and explores these through case studies of Berlin and Pittsburgh.